IMPLEMENTASI MODEL PEMBELAJARAN PROJECT BASED LEARNING DALAM PENINGKATAN HASIL BELAJAR IPAS KELAS 5 SDN 2 GUMIRIH - Ahmad Nur Cahyadi; Agus Wijaksono; Andi Wapa (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2025)
This study aims to describe the essence of the implementation of the Project Based Learning learning model in improving the learning outcomes of science and science subjects in grade 5 SDN 2 GUMIRIH. The problem raised in this study is the existence of problems in the learning process such as the emergence of students' boredom with the use of monotonous learning models that cause some students to still not be able to understand the material as a whole and have an impact on the acquisition of low social science learning outcomes, so there is a need for improvement in the application of creative and innovative learning models such as the PJBL model. The method used in the study is a qualitative descriptive approach using data collection techniques in the form of observation, interviews and documentation studies. As for the analysis technique and validity of the data, it uses member checks and credibility tests. The results of the study show that the implementation of the PJBL model in grade 5 of SDN 2 GUMIRIH is in accordance with the essence of Project Based Learning itself, which focuses on creating projects that are used as the main facilitator to achieve the learning goals that have been set from the beginning. It's just that there is a difference in the use of the learning syntax, in terms of forming groups for project creation which is changed to individual project making activities. The conclusion that researchers can draw is that the implementation of PJBL in grade 5 SDN 2 GUMIRIH is in accordance with the essence of the PJBL model itself and can overcome the problems that occur and can support the improvement of social science learning outcomes of grade 5 students.